The Effect of Using Jigsaw Strategy on Cognitive Achievement, and the Attitude Towards Using Peer Teaching - Omar, Ali Alwardany Ali; AlQarni, Amani M; Alzahrani, Mohammad Ahmad; Yahya, Islam Eid Refaei (Migration Letters, 2023)
The aim of this study is to identify the jigsaw strategy in teaching, it’s effectiveness on cognitive achievement and the attitude towards using peer tutoring. The researchers prepared a teacher’s guide and a student’s book for the learning skills unit in the learning and research skills course for preparatory (first) year students at University of Imam AbdulRhman bin Faisal according to the jigsaw strategy. The researchers also prepared an achievement test and an attitude questionnaire as evaluation tools. These tools have been applied to a research sample consisting of (140) students. The results of the study showed the following: - The average scores of the experimental group (those taught using the Jigsaw strategy) and the control group (those taught using the traditional method) in the post-application of the achievement test show a statistically significant difference at the level of (0.01) , favoring the experimental group. - The average scores of the experimental and control groups on the attitude toward using peer tutoring in teaching in the post-application show a statistically significant difference, favoring the experimental group, at the level of (0.01). - There is a positive significant correlation between the achievement test scores and the measure of attitudes towards using peer tutoring in teaching for the experimental arm in the post-measurement. Considering the results of this study; The researchers presented a set of recommendations.